Selective Reduction of Southeast Sulawesi Nickel Laterite using Palm Kernel Shell Charcoal: Kinetic Studies with Addition of Na2SO4 and NaCl as Additives - Achmad Shofi; Yayat Iman Supriyatna; Agus Budi Prasetyo (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
The aim of the reduction process is to concentrate nickel at high temperatures with a certain carbonaceous material as a reducing agent. The use of chemicals like Na2SO4 and NaCl in the reduction process can increase the content and recovery of nickel in ferronickel concentrates. A selective reduction of laterite nickel was carried out in a non-isothermal and an isothermal using palm kernel shell charcoal as a reductant and with Na2SO4 and NaCl as additives. Firstly, the raw material is made into a pellet and dried in an oven at 100 °C for two hours. The pellets are weighed before and after the reduction process. The non-isothermal reduction process used the Thermal Gravimetric Analysis (TGA) method from a temperature of 100 to 1300 °C, with a heat rate of 10 °C per minute. The isothermal reduction at temperatures 500, 600, 700, 950, 1050, and 1150 °C occurred with a reduction time of 30, 60, and 90 minutes. The analysis is Inductively Coupled Plasma (ICP) to determine the content of nickel and iron from the reduction process, X-ray Diffraction (XRD) to see changes in the phases formed after the selective reduction process, and Scanning Electron Microscopy (SEM-EDX) for viewing the microstructure of the phase. The Differential Thermal Analyzer-Temperature Gravimetric Analysis (DTA-TGA) results show the endothermic at 256 °C, and the exothermic peak at 935 °C with a total mass loss of 42.15% at 1238 °C. The shrinking core model was used for the kinetic studies of the reduction process. The closest kinetic model to the experimental results is the Ginstling-Brounshtein model, with an activation energy value of 8.73 kcal/mol. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).